2008
DOI: 10.1159/000115435
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation Outcome in Prelingually Deafened Young Adults

Abstract: The outcome of cochlear implantation in patients with deafness of prelingual onset is largely unpredictable due to high individual variability. This study evaluated speech perception performances in a group of 18 prelingually deafened subjects (aged 13–30 years) which was homogeneous with respect to duration of deafness, hearing aid use before cochlear implantation, mode of communication and administration of auditory-oral speech therapy. Word discrimination length, word and sentence identification, phoneme id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
51
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 41 publications
13
51
0
6
Order By: Relevance
“…Early studies of speech perception in NT CI candidates showed little or no improvement in open set speech discrimination, though the devices and coding strategies available then were less sophisticated than those in use today [Clark et al, 1987;Waltzman et al, 1992;Zwolan et al, 1996]. Later studies demonstrate that speech perception scores do improve, though to a lesser degree than in traditional candidates [Bond et al, 2009;Santarelli et al, 2008;Teoh et al, 2004a;Waltzman et al, 2002;Yang et al, 2011]. In our group, the mean BKB score increased from 3% before implantation to 39% at 2 years, compared to average outcome scores of 80% for traditional CI candidates in our Department.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies of speech perception in NT CI candidates showed little or no improvement in open set speech discrimination, though the devices and coding strategies available then were less sophisticated than those in use today [Clark et al, 1987;Waltzman et al, 1992;Zwolan et al, 1996]. Later studies demonstrate that speech perception scores do improve, though to a lesser degree than in traditional candidates [Bond et al, 2009;Santarelli et al, 2008;Teoh et al, 2004a;Waltzman et al, 2002;Yang et al, 2011]. In our group, the mean BKB score increased from 3% before implantation to 39% at 2 years, compared to average outcome scores of 80% for traditional CI candidates in our Department.…”
Section: Discussionmentioning
confidence: 99%
“…Recipients who used oral communication as a child, had a progressive hearing loss, and wore a hearing aid in the implanted ear up to the time of surgery have been identified as more likely to achieve better speech perception scores [Caposecco et al, 2012]. Prior auditory-verbal therapy, hearing aid use, aural/oral communication, residual hearing or a slowly progressive hearing loss, and development of speech perception all reflect at least some development of the auditory and association pathways prior to loss of neural plasticity and maintenance of these pathways prior to CI [Chee et al, 2004;Clark et al, 1987;Eisenberg, 1982;Kaplan et al, 2003;Klop et al, 2007;Santarelli et al, 2008;Teoh et al, 2004b;Yang et al, 2011;Yoshida et al, 2008]. Good speech intelligibility presumably occurs secondary to reasonable auditory input during the plastic period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many cochlear implant (CI) users have excellent speech recognition in quiet (Dorman & Spahr 2006), part of this population still struggles (Teoh et al 2004a;Santarelli et al 2008;Lazard, Giraud et al 2012). Most of them are lateimplanted prelingually deafened patients, that is, with an onset of deafness before the end of the language acquisition period.…”
Section: Introductionmentioning
confidence: 99%
“…In a review by Santarelli et al of 18 prelingually deaf-implanted adolescents and young adults (age 13-30 years), cochlear implant performance at 6 months, and 1, 2 and 3 years was reported [19]. Although cochlear implant performance was found to be lower than previously published data within the literature obtained from early implanted congenitally deaf patients, phoneme identification, word and sentence identification scores improved significantly following cochlear implantation in these late implanted patients.…”
Section: Editorialmentioning
confidence: 90%